The Rest of the World sector’s role in the intersectoral flow of funds systems of the Visegrad Group countries - Przybyliński, Michał; Trębska, Joanna (Bulletin of Geography. Socio-economic Series, 2025)
The study aims to assess the involvement of the Rest of the World (RoW) sector in the economies of Poland, the Czech Republic, Slovakia, and Hungary (the Visegrad Group, V4) as manifested by its short-term impact on disposable income (and other macro categories) through exports, investment grants, and the acquisition of financial assets. We propose a method that provides unambiguous and replicable results based on a standardised accounting system that is congruent across all European countries. The starting point is the sequence of records in the System of National Accounts (SNA). Then we construct an Input–Output Table for Institutional Sectors. Finally, we build a simple input–output model and conduct a deterministic simulation that is equivalent to the hypothetical extraction method. The main conclusion is that exports are the most important channel of foreign influence on the economy.